Comparison of the effects of remimazolam and dexmedetomidine on early postoperative cognitive function in elderly patients with gastric cancer - Liao, Yong Qing; Min, Jia; Wu, Zheng Xia; Hu, Zhi (Frontiers in Aging Neuroscience, 2023)
Purpose: To assess how remimazolam and dexmedetomidine affect aged gastric cancer patients' early postoperative cognitive dysfunction. Results: At 3 and 7 days after surgery, there were no statistically significant differences in the incidence of POCD, the MMSE and MoCA scores, or the levels of TNF-α and S-100β protein between the two groups (P > 0.05). However, compared to the saline group, both groups had higher MMSE and MoCA scores and decreased incidences of POCD. These differences were statistically significant (P< 0.05). Between group R and group D, there were no statistically significant changes (P > 0.05) in the levels of TNF-α and S-100β protein at the three time points（ at the end of the surgery, one day later, and three days later）. Even though neither group's concentration of the two factors was as high as that of the saline group, the differences were statistically significant (P <0.05). At all four time points—before anesthetic induction (T0), following induction (T2), 30 minutes into the operation (T3), and at the conclusion of the surgery (T4)—the heart rate and blood pressure in group R were greater than those in groups D and C. Statistics showed that the differences were significant (P< 0.05). The dose of propofol and remifentanil, group C > group R > group D. The duration of extubation or the amount of time spent in the PACU did not differ statistically significantly (P> 0.05) between the three groups, adverse reactions such as respiratory depression, hypotension, bradycardia, agitation, drowsiness, and nausea and vomiting had the lowest incidence in group R and the highest incidence in group C (P ＜0.05). Conclusion:Remimazolam helps lower the frequency of early postoperative POCD in elderly gastric cancer patients, which may be related to reducing the inflammatory response.